Exploring the relationship between indoor air quality and physical setting in schools: a mini review - Zakaria, Intan Bayani; Jamaludin, Nazhatulzakis; Mizal Azzmi, Norazura; Ahzahar, Nadira; Hashim, Siti Zubaidah (Universiti Teknologi MARA, Perak, 2025)
Indoor air quality (IAQ) is essential in improving the well-being of pupils, as they spend a significant amount of time inside schools than in any other indoor environment except their home. However, many schools face issues related to insufficient ventilation, improper layout design, and opening position which contribute to elevated indoor pollutant levels and potential long-term health effects. These challenges highlight the need for a systematic literature review to critically analyze and synthesize existing studies, providing a comprehensive understanding of how these physical factors of schools impact IAQ parameters such as carbon dioxide and particulate matter. A systematic review was done by analyzing papers from the SCOPUS database. Information on indoor pollution levels and physical settings were extracted from 34 studies. The findings demonstrate the complex relationships between IAQ parameters and different physical factors such as ventilation strategy, window opening, tightness of door and window, floor height, building design, and finishes. By elucidating the complex relationship between IAQ and the physical setting of buildings, this study provides valuable insights for researchers, building designers, and policymakers aiming to enhance the indoor air environment and promote pupils’ health and well-being.